Rhythmic Calcium Events in the Lamina Propria Network of the Urinary Bladder of Rat Pups - Heppner, Thomas J.; Hennig, Grant W.; Nelson, Mark T.; Vizzard, Margaret A. (Frontiers in Systems Neuroscience, 2017)
The lamina propria contains a dense network of cells, including interstitial cells (ICs), that may play a role in bladder function by modulating communication between urothelium, nerve fibers and smooth muscle or acting as pacemakers. Transient receptor potential vanilloid 4 (TRPV4) channels allow cation influx and may be involved in sensing stretch or chemical irritation in urinary bladder. Urothelium was removed from rats (P0-Adult), cut into strips, and loaded with a Ca2+ fluorescent dye (Fluo-2 AM leak resistant or Cal 520) for 90 minutes (35˚ C – 37˚ C) to measure Ca2+ events. Ca2+ events were recorded for a period of 60 seconds (s) in control and after drug treatment. A heterogeneous network of cells was identified at the interface of the urothelium and lamina propria of postnatal rat pups, aged ≤ postnatal (P) day 21, with diverse morphology (round, fusiform, stellate with numerous projections) and expressing platelet-derived growth factor receptor alpha (PDGFRα)- and TRPV4-immunoreactivity (IR). Ca2+ transients occurred at a slow frequency with an average interval of 30 ± 8.6 s. Waveform analyses of Ca2+ transients in cells in the lamina propria network revealed long duration Ca2+ events with slow upstrokes. We observed slow propagating waves of activity in the lamina propria network that displayed varying degrees of coupling. Application of the TRPV4 agonist, GSK1016790 (100 nM), increased the duration of Ca2+ events, the number of cells with Ca2+ events and the integrated Ca2+ activity corresponding to propagation of activity among cells in the lamina propria network. However, GSK2193874 (1 µM), a potent antagonist of TRPV4 channels, was without effect. ATP (1 µM) perfusion increased the number of cells in the lamina propria exhibiting Ca2+ events and produced tightly coupled network activity. These findings indicate that ATP and TRPV4 can activate cells in the laminar propria network, leading to the appearance of organized propagating wavefronts.